Distribution and leaching characteristics of heavy metals in a hazardous waste incinerator. (1st December 2018) - Li, Wenhan; Ma, Zengyi; Huang, Qunxing; Jiang, Xuguang
Highlights: Most of Cu, Cr, As, and Zn remain in bottom slag, and most Pb remain in fly ash. Hg, Cd, As, Pb, and Zn transfer into fly ash mainly by evaporation and condensation. Se and Cr transfer into fly ash mainly by entrainment. High chlorine content favors the evaporation of Cu, Pb, and Zn. The leachability of heavy metals in the bag filter ash is the highest. Abstract: In this study, distribution and leaching characteristics of heavy metals (As, Cd, Cr, Cu, Pb, Se, Zn, and Hg) along flue gas cleaning systems were investigated in a hazardous waste incinerator located in Zhejiang, China. The particle size distribution, heavy metal loading, and morphological and mineralogical characteristics of solid incineration residues were assessed before and after acetic acid extraction. Results showed that Hg, Cd, As, Pb, and Zn were transmitted into the fly ash mainly by evaporation, condensation, and adsorption, while Se and Cr were mainly by entrainment. High chlorine availability in the industry hazardous waste favored the evaporation of Cu, Pb and Zn. Due to the mass ratio of the bottom slag in the incineration residues being more than 52%, most of Cu, Cr, As, and Zn remained in the bottom slag. Scarcely any Hg and less than 9.6% of Cd were found in the bottom slag. Cd was mainly retained in the fly ash and the absorbent solution of the wet flue gas desulfurization (WFGD) system while most of Pb was found in the fly ash. WFGD system had a high Hg removal efficiency and more than 74.7% of Hg was retained in the absorbent solution of WFGD system. The distinction in the distribution and migration characteristics of heavy metals between two continuous operating conditions was mainly due to the different physicochemical properties of wastes. The studied heavy metals in the bottom slag, with the exception of Zn, showed low leachability, with a leaching ratio below 2%. Cd and Zn presented the highest leachability, and over 56.2% of Cd and more than 39.5% of Zn in the fly ash were transferred into the leachate. For the each studied heavy metal, the leaching ratio in the bag filter ash was the highest.